Preliminary Screening of Antibacterial and Phytochemical Studies of Ocimum americanum Linn. - Dhulgande3, D. A. Dhale1* A.R. Birari2 and G.S. (Journal of Ecobiotechnology, 2010)
<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">The aim of the present research was focused on the antibacterial and preliminary phytochemical properties of Ocimum americanum Linn. (Lamiaceae) via in-vitro approach. Antibacterial activity was tested against, Gram +ve and Gram -ve organisms. Maximum activity was exhibited by alcoholic extract against Staphylococcus aureus followed by Bacillus subtilis and Pseudomonas aeruginosa. Chloroform and Petroleum ether leaves extract exhibited less activity. The different solvent extracts showed the presence of secondary metabolites like alkaloids, phenolic compounds, tannins, lignin, starch, saponins, flavanoids, terpenoid and anthraquinone.